Pengaruh Fasilitas Belajar Terhadap Hasil Belajar Mahasiswa Tuna Netra di Universitas Islam Negeri Salatiga - Siti Nurkhasanah; Tsania, Farida Inayati; Kamala, Shinta Shofa; Novia, Yusrina Putri; Soleh, Muhammad Nur; Nadhita, Galuh (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study analyzes the impact of learning facilities on the academic performance of visually impaired students at the State Islamic University of Salatiga. Using a mixed-methods approach, data were collected through interviews, questionnaires, and literature studies. The sample included university students, with two visually impaired students as the primary respondents. The findings indicate that learning facilities are generally adequate but still present challenges, particularly in accessing assistive technology and curriculum support. Respondents utilize screen readers to access learning materials and develop adaptive learning strategies, such as discussions with lecturers and audio recordings. Inclusive learning facilities significantly contribute to increasing motivation and academic performance among visually impaired students. This study recommends improving both physical and non-physical facilities and providing special training for educators to create a more inclusive academic environment. These findings support inclusive education policies at the State Islamic University of Salatiga.